2011
DOI: 10.1371/journal.pone.0025468
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genome Sequencing and Evolutionary Analysis of Human Respiratory Syncytial Virus A and B from Milwaukee, WI 1998-2010

Abstract: BackgroundRespiratory Syncytial Virus (RSV) is the leading cause of lower respiratory-tract infections in infants and young children worldwide. Despite this, only six complete genome sequences of original strains have been previously published, the most recent of which dates back 35 and 26 years for RSV group A and group B respectively.Methodology/Principal FindingsWe present a semi-automated sequencing method allowing for the sequencing of four RSV whole genomes simultaneously. We were able to sequence the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
71
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(81 citation statements)
references
References 49 publications
10
71
0
Order By: Relevance
“…Analysis of RSV complete genome evolutionary dynamics was conducted on a data set containing a combination of newly obtained RSV-B isolates and strains from a recent study by Rebuffo-Scheer et al (47). The latter five full-genome sequences (JN032115 to JN032117 and JN032119 and JN032120) were derived from nasopharyngeal and nasal swabs collected from patients in the Milwaukee metropolitan area.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of RSV complete genome evolutionary dynamics was conducted on a data set containing a combination of newly obtained RSV-B isolates and strains from a recent study by Rebuffo-Scheer et al (47). The latter five full-genome sequences (JN032115 to JN032117 and JN032119 and JN032120) were derived from nasopharyngeal and nasal swabs collected from patients in the Milwaukee metropolitan area.…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, as has recently been demonstrated in many other virus groups, full-genome analyses can provide valuable insights into the processes that shape viral epidemiology and evolution (45). Complete genome sequences from RSV clinical isolates have, however, been generated in sufficiently large numbers to facilitate such analyses only recently (46)(47)(48), and that work is further extended with this study.…”
mentioning
confidence: 93%
“…The strains of subgroup A can be subclassified into eight genotypes (GA1-GA7 and SAA1), as can those of subgroup B (BA, GB1-GB4 and SAB1-3) (Parveen et al, 2006). A recent study showed that subgroup A genotypes GA1, GA2, GA5 and GA7, and subgroup B genotype BA have been detected in the USA (Rebuffo-Scheer et al, 2011). In addition, our recent studies suggest that GA2, GA5 and BA are detected in most Japanese infants with ARI (Fujitsuka et al, 2011;Goto-Sugai et al, 2010;Nakamura et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of differences in genomic sequences between virus strains has also confirmed both the existence of two distinct subtypes and the widest variation in the G gene (187)(188)(189)(190)(191)(192). For this reason genotyping of RSV strains has been based on partial or complete sequencing of G (190).…”
Section: Genetic Diversitymentioning
confidence: 94%
“…The second C-terminal hypervariable region (HVR2) is sufficient for distinguishing between subtypes and has thus been used by the majority of studies investigating RSV genetic diversity (190,(193)(194)(195)(196)(197)(198)(199)(200)(201)(202)(203)(204). More recently, whole genome sequencing has also been applied to RSV strains from various clinical settings (188,189,191,192), adding valuable information to our understanding of RSV evolution.…”
Section: Genetic Diversitymentioning
confidence: 99%